Enhanced Rh-anchoring on the composite metal phosphate Y0.33Zr2(PO4)3 in three-way catalysis. Issue 19 (16th September 2019) - Puspito Buwono, Haris; Omori, Yasuhiro; Shioya, Naoki; Yoshida, Hiroshi; Hinokuma, Satoshi; Nagao, Yuki; Iwashina, Katsuya; Endo, Yoshinori; Nakahara, Yunosuke; Machida, Masato
Abstract : Rh/Y0.33 Zr2 (PO4 )3 formed a more thermostable bidentate interfacial linkage compared to the monodentate linkage that formed in Rh/ZrP2 O7 . Abstract : A series of binary metal phosphates with the general formula Ln0.33 Zr2 (PO4 )3 (Ln = rare earths) was studied as support materials for Rh in three-way catalysis in comparison to the parent compound, ZrP2 O7 (ZP). Among the investigated materials, the Y0.33 Zr2 (PO4 )3 (YZP) support exhibited the most efficient anchoring of Rh nanoparticles and a higher activity of the catalyst persisted even after thermal ageing at 900 °C. Rh nanoparticles as large as 2 nm were found to persist on YZP; however, these nanoparticles grew into much larger agglomerates (∼10 nm) when supported on ZP. Rh K-edge extended X-ray absorption fine structure (EXAFS) was used to demonstrate that the observed difference in the stabilities of the nanoparticles was related to metal–support interactions via Rh–O–P bonding. Rh/YZP formed a more thermostable bidentate linkage compared to the monodentate linkage that formed in Rh/ZP. Thus, this bidentate linkage was preserved in the thermal ageing process. This type of interfacial bond was formed in Rh/YZP but did not form when Rh was supported on other Ln0.33 Zr2 (PO4 )3 compounds, despite the similarity in the crystal structures of the binary metal phosphates. The lower crystallinity of YZP over that of the other binary metal phosphates facilitated the geometrical deformation of YZP, which may have contributed to the efficient anchoring via strong bonding of the PO4 unit to Rh. By contrast, it was difficult for the less-flexible pyrophosphate (P2 O7 ) unit, which was formed by corner-sharing two PO4 tetrahedra to bind to Rh at the metal–support interface. This result may explain why Rh supported on ZP agglomerated into large grains among the Rh catalyst-supported metal phosphate materials.